Avaliação econômica dos custos das complicações pós-transplante renal das regiões Norte e Nordeste do Brasil - Martins, Bruna Cristina Cardoso (2020)
Kidney transplantation is considered to be the best rehabilitation treatment for patients with Chronic Kidney Disease (CKD) because it increases quality of life and survival when compared to other modalities of renal replacement therapy. However, after renal transplantation, clinical and / or surgical complications may occur. This study aimed to analyze the hospital cost of complications occurring in the first four years after kidney transplantation in patients in northern and northeastern Brazil. This is a historical, economic, analytical and exploratory cohort study in which the universe was the patients with record of kidney transplantation in 2013 in the states of the North and Northeastern Brazil. It was used as the database from the Hospital Information System (SIH / SUS) of the SUS Department of Informatics, identifying patients who underwent kidney transplantation in 2013. These patients were followed through DATASUS records specifically using SIH / SUS. from 2013 to 2017. The variables analyzed were: gender, age, post-transplant readmission follow-up period (recent, intermediate and late) using Lankarini, Noorbala, Assari ( 2009) the main complications occurring within four years after kidney transplantation, and cost of hospitalizations. A total of 893 patients underwent kidney transplantation in the study regions. During the follow-up period 319 patients returned complications. Male readmission occurred more frequently, representing 63.6% (n = 203). The average age was 45 years old (± 15.14). Patients returned complications, especially in the post-transplant period classified as “recent” (70.22%; n = 224). The number of hospitalizations was 758. The main complications that occurred were related to: urinary tract (72.02%; n = 546), infections (19.79%; n = 150) and pulmonary vascular (2.90%; n = 22). The total cost of treating these complications was R$ 1,747,713.45. It is observed that complications related to the urinary tract occupied the largest cost and impact on the total cost (R $ 1,258,752.11; 72.02%). The Northeast region had the highest cost involved (R$ 1,368,684.66). Through the analysis of SIH / DATASUS data, it was possible to identify the “recent” period after renal transplantation as the most frequent readmission and urinary tract complications as the main reason identified in the northern and northeastern regions of Brazil. In addition, there is a significant cost involved in treating these complications.